The effect of postmenopausal hormone therapy with or without folic acid supplementation on serum homocysteine level - FAK, ALİ SERDAR; HAKLAR, GONCAGÜL (TAYLOR & FRANCIS LTD, 2005)
Objective To evaluate the effects of postmenopausal hormone therapy (HT) with or without the addition of folic acid (FA) on serum homocysteine levels in a randomized, placebo-controlled design. Additionally, a non-randomized control group with no treatment was included. Methods Forty non-hysterectomized healthy postmenopausal women were randomly allocated to receive either oral continuous combined HT (0.625 mg conjugated equine estrogen with 2.5 mg medroxyprogesterone acetate daily) and oral folic acid (5 mg/day, n = 20) or HT and placebo (n = 20) for 3 months. A control group (n = 15) did not receive any study medication and was followed in the same manner. The fasting total serum homocysteine level was measured by fluorescence polarization immunoassay with a sensitivity of < 0.5 mu mol/l. Serum levels of folate, estrogen and lipid profile were also followed. Results The mean age of the postmenopausal women was 52 +/- 6 years. Baseline homocysteine level was the highest in the HT + FA group (9.96 +/- 2.82 mu mol/l), compared to HT + placebo (9.64 +/- 1.89 mu mol/l) and control groups (9.01 +/- 1.83 mu mol/l) (ANCOVA, p=0.022). Low baseline folate and vitamin B12 levels contributed significantly to the high level of baseline homocysteine in the HT + FA group. The addition of FA to HT led to a significant decrease in the serum homocysteine level from the baseline level of 9.96 +/- 2.82 mu mol/l to the final level of 8.92 +/- 2.53 mu mol/l (p = 0.023). On the other hand, HT alone (HT + placebo group) significantly increased the serum homocysteine level from 9.64 +/- 1.89 mu mol/l to 10.22 +/- 1.77 mu mol/l without a decline in serum folate level (p = 0.045). The serum homocysteine level in the control group did not change significantly (from 9.01 +/- 1.83 mu mol/l to 9.58 +/- 2.05 mu mol/l, p = 0.29). Conclusions Three months of oral continuous combined FIT increased the fasting total serum homocysteine level without affecting the serum folate level. Lowering the homocysteine level in postmenopausal woman on HT is achievable by folic acid supplementation.
Keywords: menopause; hormone therapy; folic acid; homocysteine; ESTROGEN PLUS PROGESTIN; REPLACEMENT THERAPY; PLASMA HOMOCYSTEINE; NORETHISTERONE ACETATE; DISEASE; 17-BETA-ESTRADIOL; RALOXIFENE; WOMEN; METABOLISM; TIBOLONE